An introduction to urban housing design : at home in the city - Towers, Graham (Architectural Press, 2005)
This clear and concise guide is the ideal introduction to contemporary housing design for students and professionals of architecture, urban design and planning. With the increasing commitment to sustainable design and with an ever-increasing demand for houses in urban areas, housing design has taken on a new and crucial role in urban planning. This guide introduces the reader to the key aspects of housing design, and outlines the discussion about form and planning of urban housing. Using chapter summaries and with many illustrations, it presents contemporary concerns such as energy efficient de.